Soft Skills and Graduate Employability: Insights And Research Model - Rafah AKOUM (Communications of International Proceedings, 2023)
In a fast-changing landscape of a globalized world, disrupted by global crisis, the primary challenge for today's youth lies in their ability to secure job opportunities and ensure career advancement. Hence, "hard skills" are no longer enough. Individuals must also possess a range of "soft skills" to navigate the contemporary job market effectively.  In this context, the main objective of this study is to show the increased importance of the appropriate skills wanted in the labor market in today’s employment environment. It aims to examine the level of awareness of students about their soft skills and its impact on graduate employability. First, it clarifies the ambiguous concepts of soft skills and graduate employability. A research model that can enhance graduate employability is also proposed. Second, it aims to compare students’ perceptions regarding the importance of soft skills and the crucial soft skills in demand for the period 2023-2027 by French employer’s expectations identified by the World Economic Forum (2023). This study adopt a quantitative research design. An online questionnaire survey is taking place during the month of November 2023 and concerns a sample of university students from a wide range of academic disciplines such as management, social sciences and humanities, architecture, English literature… There is 32 questions covering the soft skills and employability variables. Demographic variables were also included, covering information on gender, age, work experience and the employee’s position. A regression analysis will be conducted in order to validate the conceptual model and to explain the impact of personal, social and methodological skills on youth employability.
Keywords: Soft skills; graduate employability; student’s perception